Establishment of a platform of non-small-cell lung cancer patient-derived xenografts with clinical and genomic annotation. (October 2018) - Kang, Han Na; Choi, Jae Woo; Shim, Hyo Sup; Kim, Jinna; Kim, Dae Joon; Lee, Chang Young; Hong, Min Hee; Park, Seong Yong; Park, A-Young; Shin, Eun Joo; Lee, Seo Yoon; Pyo, Kyoung-Ho; et al.
Highlights: We established 41 NSCLC PDXs by directly implanting tumor specimens of patients. These established PDXs were genetically and clinically annotated. The clinical response was recapitulated by PDXs. PDXs is a robust tool for biomarker, therapeutic target, and drug discovery. Abstract: Background: Preclinical models that can better predict therapeutic activity in clinical trials are needed in this era of personalized cancer treatment. Herein, we established genomically and clinically annotated patient-derived xenografts (PDXs) from non-small-cell lung cancer (NSCLC) patients and investigated whether these PDXs would faithfully recapitulate patient responses to targeted therapy. Methods: Patient-derived tumors were implanted in immunodeficient mice and subsequently expanded via re-implantation. Established PDXs were examined by light microscopy, genomic profiling, and in vivo drug testing, and the successful engraft rate was analyzed with the mutation profile, histology, or acquisition method. Finally, the drug responses of PDXs were compared with the clinical responses of the respective patients. Results: Using samples from 122 patients, we established 41 NSCLC PDXs [30 adenocarcinoma (AD), 11 squamous cell carcinoma (SQ)], among which the following driver mutation were observed: 13 EGFR-mutant, 4 ALK-rearrangement, 1 ROS1-rearrangement, 1 PIK3CA-mutant, 1 FGFR1-amplification, and 2 KRAS-mutant. We rigorously characterized the relationship of clinical features to engraftment rate and latency rates. The engraft rates were comparable across histologic type. The AD engraft rate tended to be higher for surgically resected tissues relative to biopsies, whereas similar engraft rates was observed for SQ, irrespective of the acquisition method. Notably, EGFR-mutants demonstrated significantly longer latency time than EGFR-WT (86 vs. 37days, P = 0.007). The clinical responses were recapitulated by PDXs harboring driver gene alteration (EGFR, ALK, ROS1, or FGFR1) which regressed to their target inhibitors, suggesting that established PDXs comprise a clinically relevant platform. Conclusion: The establishment of genetically and clinically annotated NSCLC PDXs can yield a robust preclinical tool for biomarker, therapeutic target, and drug discovery.